Identification of Marine Landforms as a Form of Coastal Area Management in Pangandaran District - Hakim, Erwin Hilman; Darsiharjo, Darsiharjo; Yani, Ahmad; Nandi, Nandi (Tunas Geografi, 2024)
Changes in marine landforms in coastal areas are relatively rapid and need to be analyzed to determine environmental management policies. Complex marine landforms are found in the coastal areas of Pangandaran Regency and have strong pressure to fulfill community activities, not only for local communities but also for outside communities. Basically, community activities are adapted to regional environmental conditions. The aim is to optimize the potential of natural resources and minimize environmental degradation, but in reality, this has not been fully implemented. The method used in this research is a descriptive method using a field survey approach. Marine landforms resulting from the accretion process in the Pangandaran coastal area are spit landforms, aeolian-marine sedimentation in the form of coastal dunes, fluvio-marine sedimentation in the form of estuaries and alates, organic-marine landforms and white sand beaches associated with reefs. The landforms resulting from erosion are Cliffs, notches, wave-cut platforms, stacks, and stumps. The impact of landforms resulting from sedimentation in the Pangandaran coastal area is mainly spit landforms that cover river mouths and the occurrence of flooding, puddles, and even accumulation of organic waste, landforms resulting from erosion, the impact of which is the decline of the coastline accompanied by avalanches of material towards the sea, especially on beaches that have non-resistant rocks such as sedimentary rocks and alluvial deposits. Management of the Pangandaran coastal environmental area must be carried out in an integrated manner, land buritan (hinterland), which has steep slopes and resistant rock, is designated as limited production land, and the development of the spit at the river mouth is made into a jetty, and the beach has beach cups waves with rip currents and water bathymetry. -10 meters above sea level, a wave-protecting wall must be built, and the coastal border area must be used as vegetative-based conservation land.Keywords:  Marine landforms, Coastal Management, Pangandaran